The poodle of doom - Tan, Susan; Wei, Wendy Tan Shiau (New York : Scholastic Inc., 2022)
Lucy's grandmother and her poodle Fluffy arrive for a visit, and Fluffy immediately begins building a doomsday machine that will hypnotize humans and turn them into agents of chaos--can Ember work with the other pets to outsmart this evil genius?
Grades 2-3.
Keywords: Dogs -- Juvenile fiction; Pets -- Juvenile fiction; Dogs -- Fiction; Pets -- Fiction